A study on a calculus for the Tk,x,y,z-operator - Khan, Mumtaz Ahmad; Rouhi, Bijan (Pontificia Universidad Católica del Perú, 2006)
The present paper deals with the calculus of Tk,x,y,z - operator. The operator is a three variable analogue of the operator given earlier by W. A. Al-Salam [1] and H. B. Mittal [10]. The operator is useful for finding operational representations and generating functions of polynomials of three variables and will be dealt in a separate communication.
Keywords: Differential Operators; Special Functions; Generating Functions; https://purl.org/pe-repo/ocde/ford#1.01.00